Penerapan Senam Lantai dan Senam Kesegaran Jasmani untuk Meningkatkan Keterampilan Gerak Dasar, Kebugaran, dan Kesehatan Siswa di SD Negeri 060913 Medan Tembung - Rahmadani, Dwi Rizky; Adilla, Adilla; Hasibuan, Nazia Hapni; Fahmi, Rizki; Suyono, Suyono (LPPPI Publishing, 2025)
Physical education (Penjas) has an important role in developing students' physical skills and fitness, one of which is through floor exercises and physical fitness exercises. This research aims to determine the application of floor exercises and physical fitness exercises in improving basic movement skills, physical fitness and student health at SD Negeri 060913 Medan Tembung. The main problem faced is the lack of students' understanding of the basic techniques of floor exercise and physical fitness exercises as well as the lack of structured physical activity. This research uses a qualitative method with an observation and interview approach to sports teachers and students. The results of the research show that the application of floor exercises and physical fitness exercises carried out regularly and in a structured manner can improve basic movement skills, physical fitness and student health. Students demonstrated increased ability in basic movements such as rolling, somersaulting, and body balance, and experienced increased endurance and overall fitness. This research suggests that future research can explore more deeply the factors that influence the successful implementation of this activity and expand the variety of other sports activities to increase student involvement in physical education learning.